IMPACT OF TYPE OF HEMODILAYSIS ACCESS ON HRQOL ON PATIENT S UNDERGOING HEMODIALYSIS - Arif, Anum; Zafar, Misbah; Munir, Nayab Malik; Khalid, Javeria; Salman, Amna; Bhatti, Ahsin Manzoor (Pakistan Armed Forces Medical Journal, 2022)
OBJECTIVE The aim of the study was to measure the relationship between the type of vascular access and HRQOL in patients undergoing dialysis in a tertiary care hospital STUDY DESIGN Cross-sectional study PLACE AND DURATION OF STUDY Department of Vascular Surgery and Nephrology from January 2021 till June 2021 PATIENTS AND METHODS Data was collected by dialysis center nurse and duty doctors on patients meeting the inclusion criteria . It was a short form survey 36 ( SF -36 ) questionnaire which included health related quality if life in terms of physical symptoms, social functions and access related complications in last 4 weeks on a score of 0 to 3 .Higher scores means poorer quality of life. RESULTS A total of 80 patients were recruited in the study. A total of 80 patients participated in the study. Male predominance was observed ( n = 59, 73.8 % ). Mean age was 53 +/− 13.9 . 2. Mean HRQOL score in AVF 3.8 +/− 4.8 which was the lowest followed by tunnelled dialysis catheter ( TDC) 9.7 +/−4.5 and non tunnelled double lumen catheter( NTDC ) 11.8 +/−9.1 . CONCLUSION The HRQOL assessment in ESRD patients can inform the medical personnel of the effectiveness of treatment interventions, it also plays an important role in improving patient’s care, assessing patient’s needs, setting treatment goals and monitoring disease progression.